Mutual regulations between Toxoplasma gondii and type I interferon - Song, Lingling; Wang, Ruoyu; Cao, Yuanyuan; Yu, Li (Frontiers in Immunology, 2024)
In the decades since the discovery, Type Ⅰ interferon (IFN-Ⅰ) has been intensively studied for their antiviral activity. However, increasing evidences suggest that it may also play an important role in the infection of Toxoplasma gondii, a model organism for intracellular parasites. Recent studies demonstrated that the induction of IFN-Ⅰ by the parasite depends on cell type, strain genotype, and mouse strain. IFN-Ⅰ can inhibit the proliferation of T. gondii, but few studies showed that it is beneficial to the growth of the parasite. Meanwhile, T. gondii also can secrete proteins that impact the pathway of IFN-Ⅰ production and downstream induced interferon-stimulated genes (ISGs) regulation, thereby escaping immune destruction by the host. This article reviews the major findings and progress in the production, function, and regulation of IFN-Ⅰ during T. gondii infection, to thoroughly understand the innate immune mechanism of T. gondii infection, which provides a new target for subsequent intervention and treatment.